Los recursos de lenguaje del 3D estereoscópico incorporados al lenguaje audiovisual en la era digital - Silva, Marlene Nascimento da (2021)
The research studies the specific language resources of the stereoscopic 3D technique (3DE) and the aesthetic strategies for the narrative design of Argentine animated feature films made and exhibited in stereoscopic 3DE during the first two decades of the 21st century. The 3DE technique is contextualized in the specificity of the historical, whose conceptual origin dates to the very beginnings of cinema. It breaks down and analyses the narrative resources of this technique, which are incorporated into the audio visual language in the context of digital technology and which make it possible to sustain the process of design, production and exhibition of films in stereoscopic 3D. The object of study is approached, from an analysis of the plane as a minimum unit of audio-visual discourse, to reveal the experience in development of the use of these specific language resources of the 3DE technique. Likewise, the planes in which the presence of negative parallax is detected are broken down, and the design is analyzed from the perspective of the specific design tools of the animation project: the story board, the sound synchronism, the layout and the layered composition. Likewise, the observing subject is approached, and the relationships established between the body immersed in the observation and the content observed are analyzed. The research thus manages to identify design patterns in the use of specific audio visual language resources, in said technique and provide knowledge regarding the desire for representation that the 3DE technique, offers to narrative quality and for the construction of audio-visual discourse. On the other hand, it reveals aspects of visual and audio-visual language and the impact of technology on artistic practices, combining disciplines, perspectives, and approaches such as film theory, communication theory, image theory, history of art and aesthetics. The research allows conclusions to be drawn about the relationships between the stereoscopic 3D language resources incorporated into audio-visual language in the digital age and that substantially influence the design of this type of audio-visual pieces.